Delivering Therapeutics to the Cochlea: The Importance of the Patient’s Perspective - Duran, Marie-Josée; Holme, Ralph (Frontiers in Cellular Neuroscience, 2019)
Hearing loss represents a major sensory impairment in humans with a strong impact on quality of life. The current standard of care for chronic sensorineural hearing loss is limited to hearing aids and implantable devices like cochlear implants. Treatments for acute hearing loss consist of systemic or intratympanic corticosteroids. Emerging therapies are being developed to prevent hearing loss or to restore it at the cellular level. Many challenges and questions remain as to the delivery of these therapeutics into the inner ear. Scientists, clinicians and industry stakeholders should always consider the treatment burden from the patient’s perspective when designing new drug delivery approaches. This article highlights key issues to consider.